Urgensi Penggunaan Mediasi dalam Penyelesaian Perkara Pembatalan Perkawinan di Pengadilan Agama - Nugraheni, Destri Budi (Fakultas Syariah IAIN Purwokerto, 2020)
The annulment of marriage is one of the exception cases within the obligation of using mediation based on the Supreme Court Regulation No. 1 of 2016. However, after 2016, there was the annulment of marriage court decisions still used mediation for its settlement. The aim of this research is to analyze the urgency of using mediation within the annulment of marriage settlement in the Religious Court and its relevance with upholding justice for justice seekers. The method of this research is juridical normative through analyzing the secondary data namely regulations and court decisions on annulment of marriages either with or without mediation. The results showed that there was no single successful mediation in resolving cases of marriage annulment and there was no difference in the reasons for filing a case between decisions using mediation or without mediation. Regarding the function of mediation that claims to give justice for justice seekers and reduce the accumulation of cases in the Supreme Court, it can be concluded that cases of marriage annulment should not use mediation in the settlement of the case, because it is related to the legality of a marriage, not related to marital disputes.